Human resource management at the crossroads challenges and future directions - López-Cabrales, Alvaro; Valle-Cabrera, Ramon (Cambridge Scholars Publishing, 2019)
This book contains a selection of theoretical and empirical studies that highlight a number of complexities and challenges for Human Resource Management (HRM) in organizations. It serves to illustrate the difficulty in explaining the role of human resources and the complexities implicit in the management of people working together, highlighting several challenges that HRM managers face today. Several chapters provide an accurate picture of relevant topics and issues, by putting together different approaches and levels of analysis that undoubtedly enrich one another.